If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8h + -6 = 0 Reorder the terms: 5 + -6 + -8h = 0 Combine like terms: 5 + -6 = -1 -1 + -8h = 0 Solving -1 + -8h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -8h = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -8h = 0 + 1 -8h = 0 + 1 Combine like terms: 0 + 1 = 1 -8h = 1 Divide each side by '-8'. h = -0.125 Simplifying h = -0.125
| 3a-10=x-3 | | -22y=8 | | 6=.5x-3 | | 4y+(3y-44)+y=180 | | (w-4/9)*-2/3=4/5 | | 12=3(3n-5) | | 2d+3d=15 | | (w-4/9*-2/3=4/5 | | 3p^2+10p-4=0 | | Y=0.2(3.8) | | 12/(5-8)-4(-2) | | -5+2+3d-8d= | | -15.3=-7.5k+55.1 | | -2-5i/3i=0 | | 5y^2-108=0 | | 8x-5x=19+11 | | 3500.00(x+20.00)=217000.00 | | 10x^3-4x^2-6x= | | (x+5)*3= | | 4y+(3y+44)+y=180 | | 0.6*(r+0.2)=1.8 | | q=7q | | (4p-4/p)*(9p-9/4p^2) | | 0=-16x^2+32 | | 6.9=89.7y | | 2=(-3x)+5 | | 0.14285714285714290= | | 5(x-3)+6=-4(-2x+6) | | 2y+x+9=98 | | -2x-6+3x= | | 3a^2b^2-7ab= | | 3(4r-8)=36 |